Stratigraphic micropaleontology of Atlantic basin and borderlands - Swain, Frederick M. (Frederick Morrill), 1916-2008 (Developments in palaeontology and stratigraphy ;, 1977)
Stratigraphic micropaleontology of Atlantic basin and borderlands.